Pendekatan Ekosistem Pada Pengelolaan Perikanan Tongkol Skala Kecil Melalui Penilaian Domain Teknik Penangkapan Ikan Di Perairan Bali Timur: An Ecosystem Approach to Small-Scale Cob Fishery Management through the Assessment of the Fishing Technique Domain in East Bali Waters - Roni Adi Samba; Ni Luh Watiniasih; Made Ayu Pratiwi (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2021)
Karangasem's fishery potential is very large due to the large distribution of small-scale cathing fisheries areas along the coastal areas of Karangasem. The purpose of this study was to see the condition of small-scale tuna fisheries through the status of the fishing domain which refers to the Ecosystem Approach Fisheries Management (EAFM). Based on the results of the calculation of the composite value, the domain status of fishing techniques in East Seraya Village obtained a score of 68.62. These results indicate that the EAFM status of the fishing technique domain in East Seraya Village is categorized as good. However, from the results of the assessment, there are still two indicators that have bad status. This is due to the assessment of indicators of modification of fishing gear >50% of fish catches of fishermen in East Seraya Village are under Lm. And the indicators of Fishery Capacity and Catching Efforts show conditions that have been overcapacity